Verbal learning across the lifespan: an analysis of the components of the learning curve. Issue 2 (3rd March 2016) - Blachstein, Haya; Vakil, Eli
Abstract: Previous studies on the acquisition process of verbal material, conducted separately on child and adult populations, reveal that the lifespan is characterized by an inverted-U performance curve with similar achievements at its two poles. To clarify the acquisition mechanism across the entire lifespan, the learning curve for the Rey Auditory Verbal Learning Test was reproduced for participants aged 8–91. The study utilized typical trial summary scores and a more refined analysis of trial-by-trial single-word recalls, including omissions (missed words that were previously recalled), additions (recalled words previously missed), and touched words (a count for the first recall time only, for each word during the five learning trial). A clear age effect was shown for the number of words recalled – symmetrically increases during childhood and decreases in adulthood. Similarly, increased turnover of words omitted and added characterized both incremental and decremental age differences. Measurement patterns differed for the age segments on the two sides of the lifespan, despite the similar total number of words recalled by the two sides. Acquisition pattern in children was characterized by a higher number of touched words and higher turnover than for adult groups. In contrast, older adults achieved fewer touched words and lower turnover than the child groups. This study shows that it is possible to reach the same quantitative results via different cognitive processes. The results are interpreted in terms of specific mechanisms of maturational characteristics.